(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In the south of the Cantabrian region, on the border with the turmogi and vaccei, there seems to have been four oppida (Monte Bernorio, Monte Cildá, Amaya and La Ulaña), whose main characteristic is not only their large size but also the fact that they are situated close to each other. Therefore they have been considered by traditional historiography as contemporary and, hence, have been linked to the Cantabric wars (29-19 B.C.). Rather than giving another overview of the fragmentary traditional reports, this work adopts a new approach to explore the problem by spatial analysis. This allows us to understand the control of the territory as a deterrent factor of this contemporarity.